Cultural diversity, endogenous knowledge systems and learning for African development: multiple views from the South - Rwabyoma, Asasira Simon (Ciência & Trópico, 2013)
ABSTRACT The paper is based on two research questions. The first deals with how Africa’s cultural diversity can survive the cultural erosion brought about the globalization. The other question deals with how endogenous knowledge systems – the ground from which cultures and civilizations spring, can be harnessed for learning in Africa’s development process. These questions are the point of departure for the theoretical discussions that follow in this paper and call for the discussion of culture, knowledge and development in the Global South. The analysis starts with a summary of the case studies within the Great Lakes Region in Africa, and Western Africa. Then follows a theoretical discussion of the concepts of: Endogenity within African development explains how endogenous knowledge systems are spring from which culture and civilisation; Modernity and disembedding of culture, which is how social relations are lifted out of their local interaction; Politics of cultural knowledge homogenization, a section that raises the question if we are witnessing processes of homogenization of cultural starting with slave trade as one of the worst episodes in human history that destroyed African culture; Endogenous Learning for South development, this section emphasizes the need for Africa to harness endogenous knowledge systems in learning for development. The paper proposes mechanisms in promoting cultural African autonomous development, cultural dialogue with in a human rights based approach, building of Government, civil society and private sector partnerships in preserving cultural knowledge resources, among others. KEYWORDS: Culture. Endogenous knowledge. Learning. Endogenous development RESUMO O trabalho é baseado em duas questões de pesquisa. A primeira trata de como a diversidade cultural da África pode sobreviver à erosão cultural provocada pela globalização; e a segunda lida com os sistemas endogênicos de conhecimento – o campo em que culturas e civilizações nascem pode ser aproveitado para aprendizagem no processo de desenvolvimento da África. Essas perguntas são o ponto de partida para as discussões teóricas que se seguem neste trabalho e para a chamada para discussão de conhecimento, cultura e desenvolvimento no Sul global. A análise começa com um resumo dos estudos de caso na Região dos Grandes Lagos, na África, e na África Ocidental. Depois, segue-se uma discussão teórica sobre os conceitos de: a endogeneidade dentro do desenvolvimento africano explica como sistemas de conhecimento são a nascente a partir da qual a cultura e a civilização fazem parte; a modernidade e desencaixe da cultura, que é a forma como as relações sociais são retiradas do seu local de interação; a política de conhecimento cultural, uma seção que levanta a questão se estamos testemunhando processos de homogeneização cultural da partida com o comércio de escravos como um dos piores episódios da história humana, que destruiu a cultura africana; a aprendizagem endógena para o desenvolvimento do Sul, nessa seção se enfatiza a necessidade da África para aproveitar sistemas endógenos de conhecimento no aprendizado para o desenvolvimento. A pesquisa propõe mecanismos para a promoção cultural autônoma do desenvolvimento africano, o diálogo cultural com uma abordagem baseada nos direitos humanos, a construção do governo, sociedade civil e parcerias do setor privado na preservação dos recursos culturais do conhecimento, entre outros. PALAVRAS-CHAVE: Cultura. Conhecimento endógeno. Aprendizado. Desenvolvimento endógeno.